A multi-disciplinary examination of an elite triathlete`s preparation for the Hawaiian Ironman Triathlon - Coutts, A. J.; Abt, G. A.; Reaburn, P. R.; Humphries, B.; Holmes, M. A.; Mummery, W. K.; Schofield, G. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
The present study examined a number of anthropometrical, physiological and biochemical markers of overtraining in a professional triathlete leading into the 1997 Hawaiian Ironman Triathlon (HIT). The participant`s physical characteristics (height, body mass, and skinfolds) were measured by an accredited anthropometrist. Physiological parameters measured were maximal oxygen uptake (VO2max) and anaerobic threshold (AT). Oxygen uptake was determined using an incremental cycle test to exhaustion. Blood lactate measures were taken from capillarised fingertip blood during the last minute of each workload and analysed using an Accusport Lactate analyser. Anaerobic threshold was determined using the DmaxTEM method. Biochemical markers measured included an iron profile, haematology and hormones (Table 1). Venous blood samples were collected post-prandially at 9-am following a rest day. All measures were taken within the same week of training. Training consisted of three, four-week macrocycles with testing completed during the last week of each cycle. Results (Table 1) suggest that training volumes and intensities during the first two macrocycles were effective in producing positive adaptations. However, results obtained during the final testing session prior to HIT revealed that the training methods employed during the final macrocycle, or the cumulative effects of a high volume of training, may have induced a state of staleness or overreaching.